The introduction of a meta-curriculum for the promotion of higher-order thinking skills in undergraduate human movement studies - Miller, Ingrid M.(Ingrid Merle) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Human movement studies) -- University of Stellenbosch, 1991.